2014
DOI: 10.5012/bkcs.2014.35.5.1317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholesterol on the Phase Change of Lipid Membranes by Antimicrobial Peptides

Abstract: Membrane disruption by an antimicrobial peptide (AMP) was investigated by measuring the 2 H solid-state nuclear magnetic resonance spectra of 1-palmitoyl-d 31 -2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC_d 31 ) in mixtures of POPC_d 31 /cholesterol and either magainin 2 or aurein 3.3 deposited on thin cover-glass plates. The line shapes of the experimental 2 H solid-state nuclear magnetic resonance (SSNMR) spectra were best simulated by assuming the coexistence of a mosaic spread of bilayers containing por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…On an intermediate timescale (t c~1 ms), it was observed in which CP and rINEPT both yielded a poor signal because of decreased T 1r and T 2 relaxation times. Subsequent studies with lipid mixtures, including cholesterol (31,(42)(43)(44) and other lipids known to introduce liquid-ordered membrane behavior (45)(46)(47)(48), found that CP and rINEPT can both endure under identical conditions, ostensibly because t c is on the fast timescale to facilitate rINEPT, although the internal lipid order parameter (S CH ) is great enough to permit CP. However, translational diffusion was not explicitly addressed in any of these studies and could make an additional contribution to 1 H and 13 C T 2 relaxation times in liposomes, helping to explain why rINEPT and CP can both be observed in some lipid populations.…”
Section: Introductionmentioning
confidence: 99%
“…On an intermediate timescale (t c~1 ms), it was observed in which CP and rINEPT both yielded a poor signal because of decreased T 1r and T 2 relaxation times. Subsequent studies with lipid mixtures, including cholesterol (31,(42)(43)(44) and other lipids known to introduce liquid-ordered membrane behavior (45)(46)(47)(48), found that CP and rINEPT can both endure under identical conditions, ostensibly because t c is on the fast timescale to facilitate rINEPT, although the internal lipid order parameter (S CH ) is great enough to permit CP. However, translational diffusion was not explicitly addressed in any of these studies and could make an additional contribution to 1 H and 13 C T 2 relaxation times in liposomes, helping to explain why rINEPT and CP can both be observed in some lipid populations.…”
Section: Introductionmentioning
confidence: 99%